Association between Lineaments and Groundwater Intrusion into Tunnel Built in Granitic Rock Mass - Hussin, H.; H. Arifin, M.; A. Jamaluddin, T.; F. A. Ghani, M.; Ismail, N. (International Journal of Engineering and Technology, 2018)
Groundwater flow is controlled by geological structures such as lineaments. Lineaments existing in and around major infrastructures can cause problems because they commonly control the flow of groundwater. A tunnel built in granitic rock mass was chosen for this study with the objective of identifying and correlating the connection(s) between existent lineaments and groundwater intrusion.Â Two methods are applied in this study, i.e. lineament interpretation and groundwater intrusion mapping along tunnels. Lineaments are interpreted manually using satellite image before being digitized in ArcGIS software. Four sets of lineaments are identified in the study area and are oriented in NW-SE, NE-SW, E-W and N-S directions. Existence of lineaments around a tunnel constructed in granitic rock mass is identified and cross-checked with location of groundwater intrusion inside the tunnel. Comparison between these outputs show that the location of groundwater intrusion is related to existent lineament(s). The groundwater flow is mostly uncontrolled and excessive. Â Â Â